Pemodelan Potensi Pendapatan Pengelolaan Sampah Berbasis Ekonomi Sirkular Dan Nilai Islam Di TPST Madiredo - Ucik Fitri Handayani; Annanda Shofi Sulthoni; Yulianto; Royyan Atabik (JURNAL ARMADA PENDIDIKAN, 2026)
This study aims to model the potential income for the community from waste management at the Madiredo Integrated Waste Management Facility by integrating a circular economy approach, Islamic values, and mathematical modeling. The methods used include a descriptive quantitative approach via simple linear regression to map the relationship between waste volume (x) and generated income (y), as well as a qualitative approach to explore the internalization of Islamic values in waste management practices. The research results indicate a positive relationship between waste volume and income, as demonstrated by the simple linear regression model. Based on data analysis for the May–June 2025 period, a mathematical model was derived with a coefficient of determination (R²) indicating the extent to which variations in income can be explained by the volume of collected waste. The analysis results show a positive relationship between waste volume and revenue with a coefficient of determination value of 71.4%. Furthermore, it was found that Islamic values such as trustworthiness, responsibility, and social benefit have been strongly internalized within the operational activities of the TPST, thereby reinforcing the sustainability of the village’s circular economy program. This study concludes that the integration of mathematical approaches and spiritual values is capable of optimizing local economic potential while simultaneously ensuring the sustainable preservation of the environment